Hubungan Antara Tuhan, Manusia dan Alam dalam al-Quran: Aplikasi Semantik Toshihiko Izutsu - Sahidah, Ahmad (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2017)
This article explores the relationship between God, man, and nature in the Quran in Toshihiko Izutsu's view. Using semantic analysis, this Japanese scholar used the analytic principle to get the Quran interprets its own concepts and speaks for itself. For that reason, the use of Arabic poetry to understand the basic meaning of an important word and in turn, the relational meaning needs to be presented by knowing the semantic field of the researched dilemma. From a hermeneutic point of view, Izutsu's thought shows parallels with the Muslim scholar's interpretation of the theme. By looking at the relationship between God and man in the four skeletons, ontologies, masters, ethics, and communicative, Izutsu asserts that the holy book of the Quran is not only ethical but also practice.